Pengaruh Model Pembelajaran Cooperative Integrated Reading And Composition (Circ) Terhadap Hasil Belajar Geografi Kelas X di SMA Budi Luhur Samarinda - Jehamin, Gaudensius; Syam, Muliati; Setyasih, Iya (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2020)
Learning geography in class needs to read a lot of learning resources and the teacher only presents the material tends to convey the concepts on the book. As a result, student learning outcomes are not optimal. Cooperative Integrated Reading and Composition (CIRC) learning requires students to be able to play an active role in building their own knowledge and to increase students' understanding of the material. This study aims (1). To determine the effect of the Cooperative Integrated Reading and Composition (CIRC) model on the learning geography outcomes of Class X IPS SMA Budi Luhur Samarinda, (2). This study used quantitative research with type Quasi Design Experiments. (3).The subject of this study is students of class X IPS SMA Budi Luhur Samarinda with a population of 34 students. The data analysis technique was used N-Gain. (4). Based on the results of data analysis and discussion of the research data obtained an average pre-test value of 51.17 and an average post-test value of 87.35. The study shows that Cooperative Integrated Reading and Composition (CIRC) in learning geography there is an outcomes of Class X at SMA Budi Luhur Samarinda.